Analysis of ergonomic quality coefficients of contraband detectors - Власова, Алла Олександрівна (Eastern-European Journal of Enterprise Technologies, 2012)
The article concerns the world market contraband detectors of backscattered gamma rays that are part of the search and examination equipment at customs and specialized units, where the ergonomic coefficients of contraband detectors are investigated. The quality of items is assessed from the standpoint of competitiveness and global technological level. Determining the level of item, the comparison of the quality coefficients of future products and the base sample is carried out. The analysis of the ergonomic properties of portable devices of inspection control, presented as one-block designs with optional display, two-block designs and corresponding normative documentation, made it possible to form the basic coefficients of the sample quality according to the subgroup of ergonomic coefficients, including physiological, psychophysiological and health indicators for two-block contraband detector.